Limited Potential or Unfavorable Manipulations? Strategies Toward Efficient Mesenchymal Stem/Stromal Cell Applications - Lavrentieva, Antonina; Hoffmann, Andrea; Lee-Thedieck, Cornelia (Frontiers in Cell and Developmental Biology, 2020)
Despite almost 50 years of research and over 20 years of pre-clinical and clinical studies, the question of curative potential of mesenchymal stem/stromal cells (MSCs) is still widely discussed in the scientific community. Non-reproducible treatment outcomes or even absence of treatment effects in comparison to control groups challenge the potential of these cells for routine application both in tissue engineering and in regenerative medicine. One of the reasons of such outcomes is non-standardized and often disadvantageous ex vivo manipulation of MSCs prior therapy. In most cases, clinically relevant cell numbers for MSC-based therapies can be only obtained by in vitro expansion of isolated cells. In this mini review we will discuss point by point possible pitfalls in the production of human MSCs for cell therapies, without consideration of material-based applications. Starting with cell source, choice of donor and recipient as well as isolation methods, we will then discuss existing expansion protocols (2D/3D cultivation, basal medium, medium supplements, static/dynamic conditions, hypoxic/normoxic conditions) and influence of these strategies on the cell functionality after implantation. The role of potency assays will also be addressed. The final aim of this mini review is the illustration of the heterogeneity of current strategies for gaining MSCs for clinical applications with their strengths and weaknesses. Only a careful consideration and standardization of all pre-treatment processes/methods for the different applications of MSCs will assure robust and reproducible performance of these cell populations in the different experimental and clinical settings.